A New Patient Acuity Tool to Support Equitable Patient Assignments in a Progressive Care Unit. Issue 1 (January 2022) - Eastman, Debra; Kernan, Kristine
Abstract : Making fair and equitable staffing decisions and patient assignments created complexities and undue nursing dissatisfaction on a 20-bed progressive care unit. Common themes shared by the nursing staff included inadequate staffing ratios, increased workload, and unease for patient safety. On the basis of these concerns, a unit-based needs assessment provided insight into what perceived and actual barriers exist preventing nurses from providing excellent care. Information gathered helped determine what could be done to overcome some barriers, and performing a comprehensive unit profile assessment allowed for better insight into how the unit was currently functioning. A comprehensive review of literature was undertaken to examine articles related to patient acuity utilizing the electronic databases CINAHL, PubMed, and MEDLINE. Key words and phrases included the following: acuity, patient acuity, acuity tools, progressive care acuity, nurse-patient assignment, workload, nursing assignments, and equitable staffing. Utilizing the results of the nurse survey, and information gained from articles gathered during the literature review, a patient acuity tool was created. The tool was believed to be an accurate representation of the patients' acuity, and the majority of charge nurses reported that they utilized the patient acuity tool score when making nurse-patient assignments. Overall staff satisfaction and perceptions of nurse-patient assignment equity were improved.